Perencanaan Audit Atas Laporan Keuangan Pada KAP Heliantono & Rekan - Efendi, Siti Rahmah Nur; Oktapriana, Chita (JURNAL MAHASISWA BINA INSANI; Vol 8 No 1 (2023): Jurnal Mahasiswa Bina Insani (Agustus 2023), 2024)
The purpose of this study is to analyze the suitability of the planning for the audit of the financial statements of KAP Heliantono and Partners with its implementation and also the conformity with the Professional Standards of Public Accountants (SPAP). The method used in this research is descriptive analysis with a qualitative approach and the types of data used are primary data and secondary data. Primary data was collected through interviews, while secondary data was collected by collecting financial statement audit planning documents at KAP Heliantono and Partners. This study took from one of the clients to analyze the suitability of the audit plan, namely PT SNTI which was audited by KAP Heliantono and Partners in 2021. The results of this study indicate that the planning for the audit of PT SNTI's financial statements has been in accordance with the suitability of the audit planning of KAP Heliantono & Partners and the comparison of planning KAP Heliantono and Partner's audits have complied with audit standards issued by the Indonesian Institute of Certified Public Accountants (IAPI), namely SPAP.